Dual-functional adhesive containing amorphous calcium phosphate nanoparticles and dimethylaminohexadecyl methacrylate promoted enamel remineralization in a biofilm-challenged environment. Issue 9 (September 2022) - Fan, Menglin; Li, Meng; Yang, Yingming; Weir, Michael D.; Liu, Yifang; Zhou, Xuedong; Liang, Kunneng; Li, Jiyao; Xu, Hockin H.K.
Abstract: Objective: The cariogenic biofilm on enamel, restoration, and bonding interface is closely related to dental caries and composite restoration failure. Enamel remineralization at adhesive interface is conducive to protecting bonding interface and inhibiting secondary caries. This study intended to assess the remineralization efficiency of adhesive with dimethylaminohexadecyl methacrylate (DMAHDM) and nanoparticles of amorphous calcium phosphate (NACP) on initial caries lesion of biofilm-coated enamel. Methods: Artificial initial carious lesion was created via 72-hour immersion in demineralization solution and cariogenic biofilm was formed after 24-hour culture of Streptococcus mutans (S. mutans) . Specimens were then divided into 4 groups: enamel control, enamel treated with NACP, DMAHDM and NACP+DMAHDM respectively. Samples next underwent 7-day cycling, 4 h in BHIS (brain heart infusion broth containing 1 % sucrose) and 20 h in AS (artificial saliva) per day. The pH of BHIS was tested daily. So did the concentration of calcium and phosphate in BHIS and AS. Live/dead staining, colony-forming unit (CFU) count, and lactic acid production of biofilms were measured 7 days later. The enamel remineralization efficiency was evaluated by microhardness testing and transverse microradiography (TMR) quantitatively. Results: Enamel of NACP+DMAHDM group demonstrated excellent remineralization effectiveness. And the NACP+DMAHDM adhesive released a great number of Ca 2+ and PO4 3- ions, increased pH to 5.81 via acid neutralization, decreased production of lactic acid, and reduced CFU count of S. mutans (P < 0.05). Significance: The NACP+DMAHDM adhesive would be applicable to preventing secondary caries, strengthening enamel-adhesive interface, and extending the lifespan of composite restoration.